PENDIDIKAN KARAKTER DALAM ISLAM : PERSPEKTIF PEMIKIRAN IBNU KHALDUN - Miftakkhul jannah; Ahmad Mustafidin (As-Sulthan Journal of Education, 2025)
Character education is an important issue in the context of modern Islamic education, which is confronted with various social, technological, and rapidly changing values. Ibn Khaldun, a 14th-century Muslim scholar, has relevant views on character education that can be applied in the context of modern Islamic education. This research utilizes a literature analysis method to understand Ibn Khaldun's views and concepts on character education. Data were collected from Ibn Khaldun's works related to education and character, such as